Chromosome maps of globular clusters from wide-field ground-based photometry. Issue 4 (1st November 2022) - Jang, S; Milone, A P; Legnardi, M V; Marino, A F; Mastrobuono-Battisti, A; Dondoglio, E; Lagioia, E P; Casagrande, L; Carlos, M; Mohandasan, A; Cordoni, G; Bortolan, E; et al.
ABSTRACT: Hubble Space Telescope ( HST ) photometry is providing an extensive analysis of globular clusters (GCs). In particular, the pseudo-two-colour diagram dubbed 'chromosome map (ChM)' allowed to detect and characterize their multiple populations with unprecedented detail. The main limitation of these studies is the small field of view of HST, which makes it challenging to investigate some important aspects of the multiple populations, such as their spatial distributions and the internal kinematics in the outermost cluster regions. To overcome this limitation, we analyse state-of-art wide-field photometry of 43 GCs obtained from ground-based facilities. We derived high-resolution reddening maps and corrected the photometry for differential reddening when needed. We use photometry in the U, B, and I bands to introduce the Δ c U, B, I versus ΔB, I ChM of red-giant branch (RGB) and asymptotic-giant branch stars. We demonstrate that this ChM, which is built with wide-band ground-based photometry, is an efficient tool to identify first- and second-generation stars (1G and 2G) over a wide field of view. To illustrate its potential, we derive the radial distribution of multiple populations in NGC 288 and infer their chemical composition. We present the ChMs of RGB stars in 29 GCs and detect a significant degree of variety. The fraction of 1G and 2G stars, the number of subpopulations, and the extension of the ChMs significantly change from one cluster to another. Moreover, the metal-poor and metal-rich stars of Type II GCs define distinct sequences in the ChM. We confirm the presence of extended 1G sequences.